Enhancement of Cetuximab-Induced Radiosensitization by JAK-1 Inhibition. Issue 1 (December 2015) - Bonner, James; Trummell, Hoa; Bonner, Andrew; Willey, Christopher; Bredel, Markus; Yang, Eddy
Abstract Background It is known that cetuximab (an epidermal growth factor receptor [EGFr] inhibitor) is a radiosensitizer. Also, cetuximab is known to only partially inhibit the signal transducer and activator of transcription – 3 (STAT-3); a mediator of protection from apoptosis. Studies were performed to determine if the radiosensitizing effects of cetuximab could be enhanced with the addition of an inhibitor of STAT-3. Methods/Results The interaction of JAK-STAT-3 inhibition ([JAK1i]; Calbiochem, LaJolla, CA) and EGFr inhibition (cetuximab) was assessed with and without radiation. Four human head and neck cell lines were studied: UM-SCC-1 and UM-SCC-5, and two modified UM-SCC-5 lines; a STAT-3 knockdown line (STAT-3-2.4) and control (NEG-4.17). Exposure to either 0.5 μg/ml of cetuximab or 1 μM JAK1i for 8 or 24 h resulted in reduced activated STAT-3 (immunoblot), and the combination treatment showed greater reduction in activated STAT-3 compared to the individual treatments. The use of either post-radiation JAK1i (1 μM for 72 h) or post-radiation cetuximab (0.5 μg/ml) enhanced radiation-induced anti-proliferative and apoptotic effects but the greatest enhancement was seen when cells were exposed to both JAK1i and cetuximab post-radiation. Similar results were seen for radiosensitization as assessed by colony formation. Finally, the combination treatment of JAK1i (1 μM) and cetuximab (0.5 μg/ml), following radiation, resulted in an increase of unrepaired radiation-induced DNA double strand breaks at 6 and 24 h after radiation compared to the use of post-radiation JAK1i or cetuximab alone as delineated by neutral comet assay. Conclusions These findings suggest that dual inhibition of EGFr (cetuximab) and JAK-STAT-3 (JAK1i) leads to greater radiosensitization than with either cetuximab or JAK1i alone and suggests that this combination treatment may be clinically relevant even for tumors with a marked range of STAT-3 activity.